THE SPECIFICITY OF THE FUNCTIONING AND TRANSLATION OF ABBREVIATIONS IN THE ENGLISH MILITARY DISCOURSE - Avyasova Irina (Scholar Express Journal, 2023)
The purpose of this article is to develop an effective method (algorithm) for translators to decipher abbreviations in order to understand source texts, based on the nature of certain procedures and cognitive operations used in the process. The authors of this paper typifies existing military abbreviations based on their structural characteristics, establishes the cognitive operations used in the process of decoding abbreviations, analyzes abbreviations and their decoding procedures element by element to determine the order of their use, create a cognitive model of perception, understanding, and decoding by translators of unfamiliar abbreviations, and identify methods and approaches used in this process and approaches used in this process
Keywords: military terminology; graphic abbreviations; transformation-based; deciphering